The Three Postulate Idea: Between Limits and Metaphysical Beliefs in Immanuel Kant's System of Philosophy - Daunan, Duncan Matthew (Journal of World Science, 2024)
In the history of Western philosophy, debates about truth and error have continued to develop, reflecting diverse views that have emerged over time. The question of human nature became the center of intellectual attention, expanding philosophical study from speculation to fundamental thinking. Amid this context, Immanuel Kant emerged as a key figure who brought a new approach to philosophical inquiry. Although he spent his life in Koningsberg, his ideas in epistemology, anthropology, ethics, and education gained global recognition and made him one of the most influential philosophers of the modern era. However, his views have also drawn criticism, especially for the inconsistencies that are perceived to support dogmatism, although he originally intended to criticize it. This research analyzes Kant's thought, especially about the limits of human knowledge, metaphysics, and criticism of dogmatism. The method used is qualitative text analysis, which examines Kant's main work, "Critique of Pure Reason," as well as the views of other philosophers. Primary and secondary literature is reviewed to identify inconsistencies in Kant's arguments. The results show that although Kant's philosophical system has made an outstanding contribution, there are significant areas for improvement in the handling of metaphysical concepts and the limits of knowledge, which ultimately has the potential to fall into dogmatism. This study concludes that Kant's thought remains relevant and essential, but it needs to be reread critically to fully understand its impact on modern philosophy.